Tourist destination images and local culture : using the example of the United Arab Emirates - Schwaighofer, Verena (Wiesbaden : Springer Gabler, 2014)
An authentic, unique and memorable destination image is of crucial importance to be competitive in the long-term. Verena Schwaighofer analyses the currently transferred image of the United Arab Emirates as a tourist destination and to what extent the traditional Arabian culture is integrated into the image strategies of image developers in this country. First of all, a detailed theoretical overview referring to various image types, the current image transfer including critical topics related to the religion of Islam, women's role in society, behaviour, body language and dress code and the open-mindedness of the United Arab Emirates regarding local traditions related to the religion of Islam, is given. In the empirical part, a mixed method, including a qualitative media analysis (focusing on print and new media of image developers as well as newspaper articles published by journalists in the United Arab Emirates and the surrounding countries) and qualitative expert interviews are selected as appropriate research methodology. Contents Image and Destination Brands The Image of the United Arab Emirates The traditional Arabian Culture Target Groups Researchers and students in the fields of management and innovation in tourism Executives in these areas The Author Verena Schwaighofer wrote her master thesis under the supervision of Prof. Dr. Sc. Othmar M. Lehner at the Department of Innovation and Management in Tourism at Fachhochschule Salzburg, Austria.
Image and Destination Brands -- The Image of the United Arab Emirates -- The traditional Arabian Culture.
Includes bibliographical references.
Keywords: Place marketing -- United Arab Emirates; Tourism -- United Arab Emirates